2012
DOI: 10.1016/j.ultrasmedbio.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Tissue Elastography for the Diagnosis of Lymph Node Metastasis in Oral Squamous Cell Carcinoma

Abstract: We compared conventional ultrasound (US) B-mode, color Doppler and elastographic assessment of lymph node (LN) stiffness against pathological findings from surgical samples, to determine the most useful factors for identifying LN metastases. Seventy-one LNs in 19 patients with oral squamous cell carcinoma (OSCC) were examined. Using our new system, elastography images were scored from 1-5. The score 1-4 were correlated with the blue area of each LN, which indicated increased stiffness: (1) none; (2) < 50%; (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 15 publications
1
30
1
4
Order By: Relevance
“…They also found significant differences in elastography scores and portions of blue areas between metastatic and nonmetastatic LNs, revealing a sensitivity of 83.87% and a specificity of 82.50%. In our investigation, however, real-time tissue elastography revealed an even higher sensitivity which might be caused by the different anatomical regions that had been investigated (cervical LNs in the study of Ishibashi et al [35] vs. mainly inguinal LNs in our study). The usefulness of real-time tissue elastography concerning the differential diagnoses of cervical lymphadenopathy has been explored by Bhatia et al [36].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…They also found significant differences in elastography scores and portions of blue areas between metastatic and nonmetastatic LNs, revealing a sensitivity of 83.87% and a specificity of 82.50%. In our investigation, however, real-time tissue elastography revealed an even higher sensitivity which might be caused by the different anatomical regions that had been investigated (cervical LNs in the study of Ishibashi et al [35] vs. mainly inguinal LNs in our study). The usefulness of real-time tissue elastography concerning the differential diagnoses of cervical lymphadenopathy has been explored by Bhatia et al [36].…”
Section: Discussioncontrasting
confidence: 56%
“…Ishibashi et al [35] investigated the value of real-time tissue elastography for the diagnosis of LN metastases in patients with oral squamous carcinoma. They also found significant differences in elastography scores and portions of blue areas between metastatic and nonmetastatic LNs, revealing a sensitivity of 83.87% and a specificity of 82.50%.…”
Section: Discussionmentioning
confidence: 99%
“…To remedy this deficit, Ishibashi et al, (2012) raised a modification of the previously reported scoring system by Alam et al, ( 2011). Score 1, no blue area; Score 2, small blue area; Score 3, half of LN colored blue; Score 4, more than half of the LN colored blue; and Score 5, a peripheral blue area and a central red, yellow or green area (indicating obvious central necrosis).…”
Section: 5487 Clinical Value Of Real Time Elastography In Patients Wmentioning
confidence: 99%
“…Appearance of lymph node types on sonoelastography: a. benign, soft node, type 1 in all scores; b. node with less than 50% hard surface, type 2 in most scores, type 1 by Furukawa [19]; c. Node with central stiff area, occupying more than 50% of the surface, type 3 according to Alam [7] and [19], type 4 according to Ishibashi [21] and type 5 by Lenghel [15]; d. node with central elastic core and hard peripheral rim, more than 50% blue, type 4 by [7] and [21], type 3 by [19], type 5 by [15]; e. the node surface is entirely blue, type 5 by [7], type 4 by [19] and [21], type 7 by [15]; f. Node with central necrosis displaying the blue-green-red pattern, type 5 by [21], type 8 by [15], unclassified by other authors.…”
Section: Figmentioning
confidence: 99%